GENERATION AND USE OF WOOD CHIPS FROM FORESTRY RESIDUES: Energy Efficiency and Sustainability - Silva, Emerson Mateus Bezerra da; Rodolpho, Daniela (Revista Interface Tecnológica, 2025)
The transition to renewable energy sources has become a global priority in the search for sustainable alternatives to fossil fuels. Wood chips, a form of forestry waste, are emerging as a promising solution for energy generation, combining cost-effective solutions, energy efficiency, and environmental benefits. This study explores in detail the production process of these chips, from the collection of the raw material to its application in the generation of thermal and electrical energy. In addition, the environmental implications of their use, operational challenges, and market growth prospects are demonstrated. The research also discusses public policies, technological innovations, and case studies of countries that are leading the implementation of forest biomass as an energy alternative.